Cerebroumbilical doppler ratio in pregnancy induced hypertension and its prediction for adverse perinatal outcome - Salvi, Meena Bhati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To compare the changes in pulsatility index (PI) values of fetal middle cerebral artery (MCA), umbilical artery (UA) and ratio of PI of MCA and UA (cerebroumbilical ratio, C/U ratio) in normal pregnancies with pregnancy induced hypertension (PIH) and to evaluate their usefulness for predicting adverse perinatal outcome. Methods: This was a prospective comparative study carried out over a period of 1 year on total 140 patients between 30-40 weeks of gestation. Study group comprised of 70 patients with PIH. The control group comprised of 70 patients with normal BP. Both the groups were followed by doppler ultrasound and the UA PI, the MCA PI and the C/U ratio were measured. The results of the last doppler ultrasound before delivery were considered in the correlation with various adverse perinatal outcome. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of MCA PI and UA PI and C/U ratio were calculated and compared for predicting adverse perinatal outcome. Results: Abnormal C/U ratio was more common in PIH group (42.85%) than control group (5.71%). In the study group, 83.33% patients of abnormal C/U ratio showed adverse perinatal outcome. C/U ratio had highest sensitivity (75.75%), negative predictive value (80%) and diagnostic accuracy (81.42%) compared to MCA PI and UA PI for predicting adverse perinatal outcome in PIH women. Conclusions: Incidence of adverse perinatal outcome was more common with abnormal C/U ratio. C/U ratio is better predictor for adverse perinatal outcome in PIH women than individual MCA PI and UA PI.